2019
DOI: 10.1002/tesq.526
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Good Teaching Practices: Language Teacher Leadership From the Learners’ Perspective

Abstract: Teacher leadership has been given increased recognition in general education as a means to empower teachers as professionals and improve educational outcomes. However, it has not received as much attention in the field of English language teaching (ELT), and research that has been conducted in this area has tended to focus predominantly on program management. This study focused on examining learners’ perspectives of language teacher leadership with the aim of contributing to a more complete conceptualization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The second was from related research on leadership in ELT. The educational elements may include: significant changes to the ELT (Wyse & Moon, 2014), long-term instructional vision, and extra considerations to the contexts (Chan, 2021) in the support systems of standards and assessments; clear goal setting and leaders' role models (McGee et al, 2015), empowerment in ELT (McGee et al, 2015;Whitehead & Greenier, 2019), language teacher leadership (Shah, 2017), and the alignment of the instructional content, methods, and the assessments (Ni, 2017) in curriculum and instruction; ELT professional development (Slapac, 2021), instructional leaders' development, a broader professional thinking, and research team's engagement (Lesley et al, 2021) in professional development; resource supports, long-lasting external partnerships and collaborations (Slapac, 2021), dealing with crisis, and having authorities to make decisions on curriculum (Lesley et al, 2021) in environments.…”
Section: Educational Elements For Support Systems Of Ce Core Competen...mentioning
confidence: 99%
“…The second was from related research on leadership in ELT. The educational elements may include: significant changes to the ELT (Wyse & Moon, 2014), long-term instructional vision, and extra considerations to the contexts (Chan, 2021) in the support systems of standards and assessments; clear goal setting and leaders' role models (McGee et al, 2015), empowerment in ELT (McGee et al, 2015;Whitehead & Greenier, 2019), language teacher leadership (Shah, 2017), and the alignment of the instructional content, methods, and the assessments (Ni, 2017) in curriculum and instruction; ELT professional development (Slapac, 2021), instructional leaders' development, a broader professional thinking, and research team's engagement (Lesley et al, 2021) in professional development; resource supports, long-lasting external partnerships and collaborations (Slapac, 2021), dealing with crisis, and having authorities to make decisions on curriculum (Lesley et al, 2021) in environments.…”
Section: Educational Elements For Support Systems Of Ce Core Competen...mentioning
confidence: 99%
“…Research has shown that English language teachers (EFL) must have passion, rapport, purpose, balance, and adaptability to succeed in the Korean school system [26] .…”
Section: Elt Instructor Leadershipmentioning
confidence: 99%
“…Although teacher leadership is valued in general education, it is uncommon in the field of teaching English as a second language (ELT). [5] and [26] conducted empirical investigations into this concept in ELT, indicating a paucity of research in this area. According to [23], For teacher leadership in ELT, a conceptual shift is required from hierarchical and conventional leadership models to more vertical and shared leadership models.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Theorharis and Scanlan (2015) note that "school leaders include those with positional authority, such as administrators and department chairs, as well as those with relational authority, such as master teachers who have earned the respect of colleagues" (p. ix). Furthermore, Whitehead and Greenier (2019) define teacher leadership "as a dynamic set of qualities, characteristics, and behaviors exhibited inside and outside the classroom that positively influence learners not only in their learning, but also in their lives (p. 963).…”
Section: Distributed and Sustainable Leadership In The Standards And ...mentioning
confidence: 99%
“…In a third empirical study, Whitehead and Greenier (2019) build from the Christison and Lindahl (2009) and Baecher (2012) studies which explore teacher leadership in the field of English language teaching (ELT). They look at teacher leadership from the learners’ perspective and offer examples of how learners see their language teachers as leaders, as well as articulate the features and characteristics that contribute to effective language teacher leadership.…”
Section: Literature Reviewmentioning
confidence: 99%